Digital Cultural Transformation: The Role of Instructional Leadership in Improving the Quality of Educators at MTsN 26 Jakarta - Ine Rahayu Purnamaningsih; Sahrul Gunawan; Catur Yoga Meiningdias (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The digital transformation in the educational sector presents unique challenges for schools in archipelago regions, where geographical isolation often correlates with technological disparities. This study investigates the role of instructional leadership in fostering a digital culture to enhance teacher quality at MTsN 26 Jakarta, located in the Thousand Islands (Kepulauan Seribu). Employing a qualitative descriptive approach, data were gathered through semi-structured interviews, participatory observations, and document analysis. The findings reveal that instructional leadership acts as a strategic catalyst through three primary dimensions: visioning digital pedagogy, providing technology-integrated professional development, and establishing a collaborative digital ecosystem. Despite logistical constraints inherent to the archipelago context, the leadership's proactive intervention has significantly shifted the pedagogical paradigm from traditional to digital-centric. This research contributes to the discourse on educational management by providing a conceptual framework for digital culture transformation in geographically disadvantaged areas.